Handbook of reflector antennas and feed systems. Volume 3 : Applications of reflectors - Sudhakar Rao, B.; Shafai, Lotfollah; Sharma, Satish; Kane, Vicki; Bassily, S. (Artech House, 2013)
This is the first truly comprehensive and most up-to-date handbook available on modern reflector antennas and feed sources for diversified space and ground applications. There has never been such an all-encompassing reflector handbook in print, and no currently available title offers coverage of such recent research developments. The Handbook consists of three volumes. Volume III focuses on the range of reflector antenna applications, including space, terrestrial, and radar. The intent of this book volume is to provide practical applications and design information on reflector antennas used fo.